(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
In recent years, the issue of client retention has risen to prominence in the marketing literature.Customers’ wants and expectations in today’s market are always shifting, making client retention a crucialbusiness strategy. Customer retention is predicated on the idea that keeping existing customers increasesprofits by diverting resources from recruiting new ones. To increase customer loyalty, businesses needto be aware of the modern economic climate, in which consumers face reduced switching costscompared to the past. Survey research was employed as the approach. The detectives interviewed bankpersonnel in person and used a questionnaire to gauge consumer sentiment. Three hundred bank clientsfrom different institutions were used to test the tool. The data was collected using a proportionalsampling strategy. Measures of central tendency and dispersion as well as tests of significance andcorrelation are used. The purpose of this article is to learn about the most common methods banksemploy to keep their existing clients. Customer churn may be reduced and retained customers can beretained at higher rates thanks to the study’s results, which will be useful to the Indian banking industry,government, policy planners, and academics.